Strategies for Developing Destination Incentive Travel in Nias Island, North Sumatera, Indonesia - Apriliani Lase (Yayasan Literasi Sains Indonesia, 2022)
ABSTRACT (Times New Roman 10pt) Indonesia is a country that has rich marine resources, developing a deep archipelago consisting of more than 17,000 islands with 13,466 islands identified. Every region will grow and develop its potential area, one of the regions with regional potential in north Sumatra in Nias Island. Nias Island has many potential tourism objects attractive and has unique tourism potential. This study aimed to identify and analyze MICE tourism's potential strategies for incentive travel in Nias Island, North Sumatra, Indonesia. Therefore, the research objectives in this study were focusing on (1) what is the role of the government and private sector in developing tourism incentives in Nias Island? (2) how does the government's strategy for tourism development in making Nias island one of the MICE industry destinations? The results of the research found that South Nias has tremendous potential in MICE tourism activities. In addition, MICE Tourism in South Nias still requires more professional, creative, and more human resources to increase domestic and international tourists. The development of facilities and infrastructure is also necessary to support tourism activity. Research implications were also discussed. Providing full support to encourage increasing MICE activities in incentives was suggested for the government and the private sector. This study used a qualitative approach with semi-structured interviews and a case study method.